The Translocation of The Indonesian Capital City in Economic Analysis of Law Perspective - Mufidah, Nuruz Zakiyatul; Hadi, Fikri (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
In August 2019, the President of Republic of Indonesia gave speech on an idea of the translocation of the Indonesian capital city. The new capital city has also already decided by the President. The decision is made before the legal analysis including the legal basis of the decision to have new capital city. This paper will analyze about the translocation of the Indonesian capital city from the perspective of economic analysis of law. The argument in this paper is written as a socio-legal research. This paper ends up with the conclusion that the concept of the Indonesian capital city is ineffective and inefficient from the perspective of economic analysis of law. There is no legal basis of the translocation of the Indonesia capital city. Besides, the masterplan of the new capital city does not accommodate the central business district for the industrial area, whereas the industrial area, at least state-owned enterprises of Indonesia should be located near the seat of government.